TIMESCALES AND MECHANISMS OF PLUME-LITHOSPHERE INTERACTIONS: 40AR/39AR GEOCHRONOLOGY AND GEOCHEMISTRY OF ALKALINE IGNEOUS ROCKS FROM THE PARANÁ-ETENDEKA LARGE IGNEOUS PROVINCE - Gibson S.A.; Day J.A.; Thompson R.N. (My University, 2006)
We have determined high-precision 40Ar/39Ar ages for alkaline igneous rocks from the western margin of the Early-Cretaceous Paraná-Etendeka large igneous province (Paraguay). These show that small-fraction melt generation occurred beneath the region in two phases; at 145 Ma and 127.5 Ma, i.e. before and at the end of the 139-127.5 Ma Paraná-Etendeka flood-basalt eruptions. Previously published 40Ar/39Ar ages for alkaline igneous rocks on the proto-Atlantic coastal margins range from 134 to 128 Ma and indicate that small-fraction melt generation in the east of the province was either synchronous or slightly later than the main pulse of tholeiitic volcanism (between 134 and 132 Ma). Our new 40Ar/39Ar phlogopite ages confirm that: (i) the earliest melts associated with the initial impact of the Tristan plume were generated in the west of the Paraná-Etendeka large igneous province and (ii) igneous activity was long lived and immediately predates continental break-up. The Early-Cretaceous Paraguayan alkaline magmas are silica-undersaturated, enriched in incompatible-trace elements, have very-low initial εNd values and probably represent melts of phlogopite-bearing, carbonate-metasomatised peridotite in the subcontinental lithospheric mantle. Our simple one-dimensional, conductive-heating models suggest that the early-phase (145 Ma) alkaline magmas were emplaced on the margins of the Rio de La Plata craton at the time of sublithospheric impact of the proto-Tristan plume. The late phase (127.5 Ma) of Paraguayan alkaline magmatism is concentrated in an intra-cratonic rift zone and melt generation appears to have been triggered by lithospheric extension, perhaps facilitated by conductive heating and thermal weakening associated with the upwelling Tristan plume. The location and timing of both alkaline and tholeiitic melt generation in the Paraná-Etendeka province appear to have been significantly influenced by the non-uniform composition and thickness of the South American and south-west African lithosphere. The long duration of Paraná-Etendeka magmatism (17 Myr) relative to other Phanerozoic large igneous provinces (e.g. Siberia, Karoo, and Deccan) may be an artefact of the limited available high-precision age data for CFB-related alkaline igneous rocks. © 2006 Elsevier B.V. All rights reserved.
Keywords: 40AR/39AR GEOCHRONOLOGY; ALKALINE IGNEOUS ROCKS; LARGE IGNEOUS PROVINCE; MANTLE PLUME; PARANÁ-ETENDEKA; TRISTAN; Мезозой::Меловая; Mesozoic::Cretaceous